BEHAVIORAL ANALYTICS OF FINANCIAL ADVERTISEMENTS INFLUENCE THROUGH VISUAL ELEMENTS ACROSS GENERATIONAL COHORTS - Shiju, Dr. Christina; Sharma, Dr. Monali (The journal of contemporary issues in business and government, 2022)
Visual elements impact an individual’s cognitive assessment for financial decision making. Financial advertisements through a visual medium that an investor is exposed to might be amongst the myriad factors that impact the investor. The study assesses the implication of financial advertisements for decision making across cohorts. Area of interest (AOI) and visual elements have been taken for study to comprehend the data collected through a visual tracking application and through a structured questionnaire. The respondents’ attention on the imagery and their own assessment of their attention to the advertisement was determined. The subconscious impact of the imagery and their conscious assessment for financial advertisements has been studied in the paper. Generational cohorts: Generation X, Generation Y and Generation Z have been the respondent cohort and an understanding of the cognitive assessment of visual imagery across the cohorts has been studied. Deeper insights into what actually is of relevance for the attention of an investor in an advertisement has wide implications in the study of investor behavior.